Supporting the Legitimacy of Quality Criteria for Multimodal Production in School - Mikkeline Blatt Hoffmeyer; Jesper Juellund Jensen; Marie Veisegaard Olsen (Stockholm University Press, 2020)
The aim of this article is to examine the significance of teachers' conceptions of quality when assessing digital multimodal student productions. The authors have undertaken a design-based research study to examine how to support teachers' use of explicit quality criteria for multimodal production in 5th to 8th grade Danish and History classes (year 11-15). Through the development of a tool to support teachers' drawing up and use of assessment criteria for digital multimodal products, teachers' conceptions of quality of multimodal products were examined based on interviews and classroom observations. The authors propose four reasons for teachers not regarding qualities of digital multimodal genres as legitimate in school. Firstly, the relevance of product quality is not acknowledged. Second, opposing and confusing communication purposes for multimodal products in school leave no room for clear quality criteria and assessment of the products. Third, the learning potential of other modes than language is not accepted. And finally, the new digital multimodal genres are understood and assessed in the light of traditional school genres.